Antioxidant and Anticholinesterase Assets and Liquid Chromatography-Mass Spectrometry Preface of Various Fresh-Water and Marine Macroalgae - Murat, Kartal; Ilkay, Orhan; Mahmud, Abu-Asaker; Senol, F. S.; Tahir, Atici; Bilge, Sener (2009)
The ethanol extracts from the fresh-water algae; Chara hispida L., Cladophora glomerata (Dilw.) Kutz, C. fracta (Dilw.) Kutz, Spirogyra gratiana Transeau, Mougeotia sp. (C.A. Agardh), Vaucheria sessilis (Vauch.) De Candolle, Geminella mutabilis (Breb.) Wille, the fresh-water plants; Ranunculus rionii Lagger and Ceratophyllum demersum L., as well as the marine algae; Sciniaia furcellata (Turn.) J. Agardh, Dictyota dichotoma (Huds.) Lam., Padina vickersiae Hoyt, Halopteris scoparia (L.) Sauvagau, and the sea grass; Posidonia oceanica (L.) Dell. were assessed in vitro for their antioxidant and anti-acetylcholinesterase (AChE) activities. Antioxidant activity was evaluated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity test at 0.125, 0.25, 0.5, 1.0, and 2.0 mg ml(-1) and ferric-reducing antioxidant power assay (FRAP) at 0.5, 1.0, and 2.0 mg ml(-1) concentrations. Total phenolic contents of the extracts were determined using Folin-Ciocalteau's reagent. The extracts were further analyzed qualitatively by LC-DAD-MS. S. gratiana had the best antioxidant activity, followed by R. rionii. LC-DAD-MS showed rich gallic acid and its ethyl ester contents in S. gratiana, while prosperous vitamin C content has been detected in P. oceanica for the first time in this study. S. gratiana possessed the highest inhibition (42.5 +/- 2.28%) at 2.0 mg ml-1 against AChE.